Effie Hone interviewed by Sheena Grant in the Australia 1938 oral history project - Hone, Effie, 1894-; Grant, Sheena; Australia 1788-1988: A Bicentennial History; Australia 1938 Oral History Project (1982)
Dr Hone speaks of her family background; religion; childhood and school memories in Melbourne; family life and lifestyle; attending college of domestic economy; travel; experiences studying medicine at Melbourne University; employment experiences and conditions; courtship and marriage; home and living conditions; domestic servants; her children; health care; family lifestyle; entertainment and recreation; class; politics; Perth in the 1930s; overseas travel; Australia in 1938; England and Australia.
Transcript unavailable, interview summarised on cassette cover.
Recorded by the Australia 1938 Oral History Project as research for the book Australians 1938 from the series Australians, a historical library.
Digital master available
Keywords: Hone, Effie, -- 1894- -- Interviews; Women physicians -- Australia -- Biography; Australia -- Social conditions -- 1901-1945.